Inclusive students’ challenges in learning English (A case study in SD Negeri Balirejo, Yogyakarta) - Jaya, Patria Handung; Putri, Ade Berliana; Suriya, Azza Naila (English Education Department, Universitas Islam Indonesia, 2026)
The fact that the world is now borderless has increased the demand for English in society. This demand does not only apply to adults but in the Merdeka Curriculum, early childhood, elementary school students and inclusive students or students with SEN (Special Education Needs) are now also required to be able to speak English. Many researchers have discussed the various difficulties in learning English faced by adults or children, but few have discussed the difficulties experienced by SEN students, even though they have the same demands and rights as everyone else to learn English. This study aims to provide an overview regarding the challenges experienced by SEN students in learning English. Qualitative method was done by direct interviews with inclusive students and English teachers at SD N Balirejo which is one of the inclusive schools in Yogyakarta. This study proves that the use of vocabulary, pronunciation and speaking in English are some of the difficulties experienced by SEN students. In addition, students with SEN face difficulties in social interaction that makes English learning process more challenging. Therefore, an appropriate environment, methods and strategies as well as the role of teachers are needed to support English learning for inclusive students.